PERENCANAAN MANAJEMEN PROYEK DALAM PERAWATAN APU GTCP131-9B PT. GARUDA INDONESIA - Gumilang, Dicky; Timothy, Dennis (Inaque : Journal of Industrial and Quality Engineering, 2022)
The air transportation industry in Indonesia is growing rapidly and is very competitive. Aircraft fleet maintenance is an important factor in supporting airlines to compete in the local and global industry. On the other hand, delays in the completion of fleet maintenance can result in delays in flight schedules and this is very detrimental to the airline and passengers. This is a challenge for business actors in the aircraft maintenance sector because of the risk of being penalized for delays that occur. Therefore, this study aims to reduce the risk of late fines faced by aircraft maintenance business actors. With project management, the company is expected to be able to produce effective and efficient maintenance activities. This is very much needed by the company in producing optimal output and has a great impact on airlines that use aircraft maintenance services. In this study, the evaluation of project management uses the Critical Path Method (CPM), Program Evaluation and Review Technique (PERT), Work Breakdown Structure (WBS) to evaluate the preparation of aircraft maintenance activities and the Crashing method if acceleration is needed in completing maintenance activities in accordance with agreed agreement. With the preparation of good project management, it is possible to estimate the time and cost needed to complete a project so as to minimize delays and losses in completion. The project management planning used in this project resulted in an accelerated completion of 3.5 days with an additional cost of $ 8,958.23.